Popmusik- und Medienkulturen verstehen, erforschen und reflektieren. Studiengang "Populäre Musik und Medien" und Gründung des Forschungszentrums "C:POP". - Jacke, Christoph; Flath, Beate (Kulturpolitische Mitteilungen)

Quedlinburg abbey’s medieval history in ever-changing political and religious frameworks: a survey - Mersch, Katharina Ulrike (A companion to the abbey of Quedlinburg in the Middle Ages)

Who made reform visible? Male and female agency in changing visual culture - Mersch, Katharina Ulrike (Women and monastic reform in the medieval west, c. 1000-1500. Debating identities, creating communities)

Pfalz und Stift Quedlinburg in Konflikten des 10. bis 12. Jahrhunderts - Mersch, Katharina Ulrike (1100 Jahre Quedlinburg. Einblicke in das Leben auf der Königspfalz)

Perforating urban boundaries with processions - Mersch, Katharina Ulrike (Religion and Urbanity Online)

Jonathan Reinert, Volker Leppin (Hgg.): Kleriker und Laien. Verfestigung und Verflüssigung einer Grenze im Mittelalter (Spätmittelalter, Humanismus, Reformation / Studies in the Late Middle Ages, Humanism, and the Reformation 121). Tübingen: Mohr Siebeck 2021. VIII, 313 S. ISBN 978-3-16-160801-8. Leinen - Mersch, Katharina Ulrike (Rottenburger Jahrbuch für Kirchengeschichte)

Becher, Matthias / Achim Fischelmanns / Katharina Gahbler (Hrsg.), Vormoderne Macht und Herrschaft. Geschlechterdimensionen und Spannungsfelder (Macht und Herrschaft, 12), Göttingen 2021, V & R unipress / Bonn University Press - Mersch, Katharina Ulrike (Zeitschrift für Historische Forschung)

Seabourne, Gwen, Women in the Medieval Common Law c. 1200-1500 (Studies in Medieval History and Culture), London / New York 2021, Routledge - Mersch, Katharina Ulrike (Zeitschrift für Historische Forschung)

Felicity Hill: Excommunication in Thirteenth-Century England. Communities, Politics, and Publicity, Oxford University Press 2022 - Mersch, Katharina Ulrike (sehepunkte)

Die „Chronica de beato Brunone primo Cartusiensium“ Heinrich Arnoldis von Alfeld by Christoph Galle - Mersch, Katharina Ulrike (Renaissance Quaterly)

Determination and Compensation of the Shrinkage Behavior of Cylindrical Elements in the FDM Process - Koers, Thorsten; Magyar, Balázs (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
Fused Deposition Modeling (FDM) is an additive manufacturing process to produce complex thermoplastic geometries layer by layer. The filament is melted in a nozzle, iteratively deposited, and then cools down. Due to the solidification process, the deposited filament strands deviate from their intended position due to shrinkage, resulting in significant geometric deviations in the final part. In terms of dimensional accuracy, there is a need for optimization, especially for local curved geometries in relation to the global part with higher nominal dimensions. The aim of this study is to investigate the size and shape deviations for cylindrical FDM elements and to compensate the expected deformations by using an in-house software with adaptive scaling factors in the x-y plane. Previous studies mainly focus on simple, non-curved objects, this study also considers the influence of curvature and global as well as local deviations on the final part.

Depiction of support structures in technical drawings - Lammers, Stefan; Koers, Thorsten; Magyar, Balázs; Zimmer, Detmar; Lieneke, Tobias (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
To ensure uniform documentation of support structure information, a concept is presented that enables a standardized depiction of support structures in technical drawings based on ISO 128-3. To this end, requirements for a uniform depiction are defined and a procedure for drawing entry is presented. The drawing entry should contain all production-relevant support structure information. The standardized documentation of support structure information in technical drawings is intended to ensure a simple, clear and safe exchange of information between business units or different companies along the value chain. As a result a possible drawing entry of support structures was developed. To distinguish between different support structure types, a standardized depiction of geometrical information in a specification field is shown. The specification field gives a detailed description of the support structure type, the geometry as well as the connection to the part and the building platform. Also uncommon support types like lattice structures or CAD based support structures can be implemented. To ensure the usability the depictio is editable and extendable.

Lost in Transformation: Rediscovering LLM-Generated Campaigns in Social Media - Grimme, Britta; Pohl, Janina; Winkelmann, Hendrik; Stampe, Lucas; Grimme, Christian (Disinformation in Open Online Media: 5th Multidisciplinary International Symposium, MISDOOM 2023, Amsterdam, The Netherlands, November 21–22, 2023, Proceedings)
This paper addresses new challenges of detecting campaigns in social media, which emerged with the rise of Large Language Models (LLMs). LLMs particularly challenge algorithms focused on the temporal analysis of topical clusters. Simple similarity measures can no longer capture and map campaigns that were previously broadly similar in content. Herein, we analyze whether the classification of messages over time can be profitably used to rediscover poorly detectable campaigns at the content level. Thus, we evaluate classical classifiers and a new method based on siamese neural networks. Our results show that campaigns can be detected despite the limited reliability of the classifiers as long as they are based on a large amount of simultaneously spread artificial content.
Keywords: Social Media; Campaign Detection; Large Language Models; Siamese Neural Networks

Informal Street Vending in Harare - Bhila, Ishmael; Chiwenga, Edson (Interventions)

Bist du eine Hauptfigur, eine Nebenfigur oder nur ein Outtake und nie im Bilde in deinem Leben? Sophie Linnenbaums Filme als Korrespondenz zwischen Film- und realen Welten - Keuchen, Marion (theo mag . tà katoptrizómena – Magazin für Kunst| Kultur | Theologie | Ästhetik. Filmische Passionen)

Polarization in Online Social Networks: A Review of Mechanisms and Dimensions - Tölle, Laura; Trier, Matthias

A Social Network Approach for Investigating Social Influences on Effective Use: Demonstration in Virtual Reality Collaboration - Tölle, Laura; Slawinski, Elena; Fromm, Jennifer; Mirbabaie, Milad

Spectral correspondences for rank one locally symmetric spaces - The case of exceptional parameters - Hilgert, Joachim; Arends, C. (J. de l'École polytechnique — Mathématiques)

Aspects of control theory on infinite-dimensional Lie groups and G-manifolds - Hilgert, Joachim; Glöckner, H. (J. Diff. Equations)

Autonomous Golf Putting with Data-Driven and Physics-Based Methods - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (2022 Sixth IEEE International Conference on Robotic Computing (IRC))